The derivational nature of reduplication: Towards a Functional Discourse Grammar account of a non-concatenative morphological process. (March 2018) - Schwaiger, Thomas
Abstract : This article advances a first systematic Functional Discourse Grammar (FDG) treatment of reduplication. Building on cross-linguistic arguments for reduplication's iconic motivation and non-concatenative derivational nature, principled advantages of FDG's functional-typological orientation over formal reduplicative models are programmatically demonstrated: Reduplication is differentiated from repetition in FDG's architecture, the basics for implementing reduplicative iconicity into the model are outlined, and several formalizations of the process based on existing FDG work on morphological derivation are suggested. Phonological characteristics of reduplication are mentioned briefly and mostly left for future FDG research.